Why kids love (and hate) school : reflections on difference - Jones, Steven P. (Steven Paul), 1955-; Sheffield, Eric C. (Academy for Educational Studies book series., 2018)
The authors of Why kids love (and hate) school addresses the following questions: How do contemporary educational theories, policies, and practices impact the manner in which historically marginalized students perceive their schooling experiences? What theories, policies, and practices lead diverse students to hate school? Love school? Feel ambivalent about school? What might be done to create a love of school among these students as opposed to a hatred of school? Approaching these questions from a variety of perspectives, this collection consists of theoretical discussions, personal reflections, research reports, and policy suggestions sourced in the experiences of our most vulnerable students with an eye to making schools places all students might love rather than hate. The essays take up these issues from the perspective of poverty, gender, race, ethnicity, ability, language, and religion, among others. These essays also provide practical advice for teachers and administrators - both practicing and pre-service - for making classrooms and schools spaces that would encourage our students to say, "I love school." As teachers, administrators, university faculty, and researchers, the authors of this collection bring interesting and diverse viewpoints into the discussion